Understanding Tracy Letts - Fahy, Thomas Richard (Understanding contemporary American literature., 2020)
"Winner of the Pulitzer Prize in Drama as well as Tony Awards for Best Play and Best Actor, Tracy Letts has emerged as one of the greatest playwrights of the twenty-first century. In the first critical overview of Letts' theatrical oevre, Thomas Fahy contextualizes each of the plays, exploring his treatment of themes from disability to conspiracy and Native American identity to troubled masculinity. Understanding Tracy Letts is an introduction to the plays and an invitation to engage with them as moving works of art and incisive commentary on contemporary working- and middle-class American life. Chapters focus on Killer Joe; Bug; August: Osage County; Mary Page Marlowe; and Linda Vista, Superiority Donuts, and Man from Nebraska. The book also provides brief coverage The Minutes (which premiered at Steppenwolf in 2017 and will open on Broadway in 2020) and Letts' decision to write the screenplay for The Woman in the Window (premiering in 2020 and adapted from the bestselling novel of the same title by A.J. Finn)"--